A novel bioassay using the barnacle Amphibalanus amphitrite to evaluate chronic effects of aluminium, gallium and molybdenum in tropical marine receiving environments. Issue 1 (15th November 2016) - van Dam, Joost W.; Trenfield, Melanie A.; Harries, Simon J.; Streten, Claire; Harford, Andrew J.; Parry, David; van Dam, Rick A.
Abstract: A need exists for appropriate tools to evaluate risk and monitor potential effects of contaminants in tropical marine environments, as currently impact assessments are conducted by non-representative approaches. Here, a novel bioassay is presented that allows for the estimation of the chronic toxicity of contaminants in receiving tropical marine environments. The bioassay is conducted using planktonic larvae of the barnacle Amphibalanus amphitrite and is targeted at generating environmentally relevant, chronic toxicity data for water quality guideline derivation or compliance testing. The developmental endpoint demonstrated a consistently high control performance, validated through the use of copper as a reference toxicant. In addition, the biological effects of aluminium, gallium and molybdenum were assessed. The endpoint expressed high sensitivity to copper and moderate sensitivity to aluminium, whereas gallium and molybdenum exhibited no discernible effects, even at high concentrations, providing valuable information on the toxicity of these elements in tropical marine waters. Highlights: A novel toxicity bioassay was developed considering development of barnacle larvae. The assay generates chronic toxicity data relevant to tropical marine environments. Chronic toxicity data were generated for copper, aluminium, gallium and molybdenum. Resulting data can be used by resource managers to establish water quality guidelines. The assay may be utilized by industry for discharge licence compliance testing.